WHY DO START-UPS FAIL IN INDIA: A STUDY - Abdul Kalam, Naresh, Pavan Kumar, Abishek Kumar Singh (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The aim of this study is to why the initiative and scope of start-ups fails by various factors influences and contribute for the startups in India have failed. The majority of people in our nation choose services over businesses. Unfortunately, the value of entrepreneurship is not emphasised by our educational system. IITs, which are technical institutions, have stepped up their efforts to support entrepreneurs and the idea of self-employment. Many IIT graduates are leaving well-paying employment to launch their own businesses. However, given the nature of the education and training offered, it might not be sufficient to equip new entrepreneurs. The Indian learning process is not suited for the development of entrepreneurship. Talented individuals are available to work in the government, in the private market, or in white collar employment. There are several causes for the gloomy state of entrepreneurship in India.